ANALISIS KINERJA MANAJERIAL BERDASARKAN PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN, PARTISIPASI ANGGARAN DAN IMPLEMENTASI STRATEGI PADA PDAM TIRTA PAKUAN KOTA BOGOR - Lasmana, Andy; Nofiyati, Nofiyati (JURNAL AKUNIDA, 2017)
This study aim is analyze influence of responsibility accounting, budgetary participation, and strategic implementation to manajerial performance at PDAM Tirta Pakuan Town of Bogor. Data in this study is a primer data that is questionair and interview with relevan parties. Sample in this study is 42 respondents are the lower managers until the middle managers. Instrument in this syudy are analized by validities, reliabilities,and classical assumption. The analyze techniquesed is multiple regression analyzed and hypothesis testing with t test. The result is indicated that responsibility accounting, budgetary participation, strategic implementation have a positif significant impact to manajerial performance particially and simultan.Key words: Responsibility accounting, budgetary participation, strategic implementation, manajerial performance.